4.2 Infant neurodevelopmental outcomes following late and moderately preterm birth. (9th June 2014) - Boyle, EM; Draper, ES; Evans, TA; Field, DJ; Manktelow, B; Marlow, N; Seaton, S; Smith, LK; Johnson, S
Abstract : Introduction: Very preterm (<32 weeks) infants are at high risk for neurodevelopmental sequelae. Less is known about outcomes following birth at late and moderately preterm gestations (LMPT; 32–36 weeks). Methods: 1130 LMPT and 1255 term-born (≥37 weeks) babies were recruited at birth to the Late and Moderately Preterm Birth Study (LAMBS). At 2-years, parents completed the Parent Report of Children's Abilities-Revised (PARCA-R) to assess cognitive impairment and a questionnaire to assess neurosensory (vision, hearing, motor) impairment. Neurodevelopmental disability was defined where the child had a moderate/severe impairment in at least one domain. Results: Parents of 651 (59%) LMPT and 771 (62%) term-born children responded at 2 years. Overall, 1.6% of LMPT infants and 0.3% of controls had a neurosensory impairment (RR 6.00; 95%CI 1.32, 27.28). Rates of cognitive impairment were higher in general (LMPT 15.6%; Term 10.0%) and LMPT infants at increased risk of cognitive delay (RR 1.56; 95% CI 1.18, 2.06). Overall, 16% of LMPT and 10% of term-born infants had neurodevelopmental disability (RR 1.57; 95% CI 1.19, 2.07). Male sex, non-white ethnicity, lower socio-economic status, pre-pregnancy hypertension, preeclampsia and recreational drug use were risk factors for neurodevelopmental disability among LMPT children. Conclusions: Children born LMPT are at increased risk for neurodevelopmental disability; although the risk was largest for neurosensory impairment, the number of children affected by cognitive problems was far greater. Preeclampsia and antenatal recreational drug use are markers of poor outcome and may be potentially modifiable factors for reducing adverse outcomes following LMPT birth.